EDUCATIONAL STRATEGIES FOR PANDEMIC PREVENTION AND PREPAREDNESS: LESSONS FROM COVID-19 FOR THE FUTURE - POSSO-PACHECO, RICHAR JACOBO (2024)
INTRODUCTION: THE COVID-19 PANDEMIC LED TO MANDATORY VIRTUAL EDUCATION; AS VACCINATION PROGRESSED, A RETURN TO IN-PERSON LEARNING WAS IMPLEMENTED WITH BIOSECURITY STRATEGIES IN PLACE. OBJECTIVE: TO ANALYZE HEALTH MEASURES AND ACTIONS IMPLEMENTED IN THE EDUCATIONAL CONTEXT DURING THE COVID-19 PANDEMIC FOR PREVENTION, PREPAREDNESS, AND RESPONSE TO FUTURE INTERNATIONAL PUBLIC HEALTH EMERGENCIES. METHODS: A SYSTEMATIC REVIEW WAS CONDUCTED FOLLOWING PRISMA 2020 GUIDELINES. DATA WERE COLLECTED FROM SCOPUS, SCIENCE DIRECT, AND GOOGLE SCHOLAR DATABASES, WITH INCLUSION AND EXCLUSION CRITERIA REDUCING THE INITIAL 341 ARTICLES TO 12 FOR ANALYSIS. RESULTS: THREE KEY STRATEGIES FOR ADDRESSING FUTURE PANDEMICS IN EDUCATIONAL SETTINGS ARE HIGHLIGHTED. PREVENTION FOCUSES ON MEASURES LIKE SOCIAL DISTANCING, MASK-WEARING, AND RIGOROUS HYGIENE TO ENSURE THE SAFETY OF STUDENTS AND STAFF. PREPAREDNESS INVOLVES ONGOING TRAINING, CLEAR PROTOCOLS, AND AVAILABLE RESOURCES. RESPONSE INCLUDES SOCIOEMOTIONAL SUPPORT FOR STUDENTS AND TEACHERS, CONTINUOUS ASSESSMENTS, AND NECESSARY ADJUSTMENTS. CONCLUSIONS: THIS STUDY PROVIDES A SOLID FOUNDATION FOR DEVELOPING PREVENTION, PREPAREDNESS, AND RESPONSE STRATEGIES IN THE EDUCATIONAL CONTEXT IN THE FACE OF POTENTIAL COVID-19 RESURGENCES AND OTHER PUBLIC HEALTH EMERGENCIES. BY IMPLEMENTING THESE MEASURES, EDUCATIONAL INSTITUTIONS WILL BE BETTER PREPARED TO ENSURE CONTINUITY OF EDUCATION AND PROTECT THE HEALTH OF STUDENTS AND STAFF IN A WORLD FACING UNKNOWN CHALLENGES. © 2024; LOS AUTORES.